2007
DOI: 10.1021/ie070154o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on the Photo-Fenton Process

Abstract: The existence or presence of diverse hydrocarbons and persistent pollutants in seawater or saline wastewater due to different industrial activities is considerable. The photo-Fenton process is suggested as a possible treatment, but the effect of salinity must be explored. An experimental design is carried out to elucidate the influence of NaCl on the efficiency of the process. According to the results, the global TOC removal is not influenced by the presence of chloride, but the process becomes much slower, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 17 publications
1
38
0
2
Order By: Relevance
“…At a high concentration of chloride ions, however, the oxidation of aniline ceased. Chloride ions slow down the oxidation reactions through the complexation of Fe 2+ /Fe 3+ with Cl − (Reactions (4)- (7)) and/or by acting as scavengers of hydroxyl radicals (Reactions (8)- (10)) (Bacardit et al, 2007;De Laat et al, 2004;Kiwi et al, 2000;Machulek et al, 2007). It can be seen from Reactions (8) and (10) that the scavenging effect of chloride ions was pH-dependent, which can be abated by maintaining the pH at an optimal level of 3 during the Fenton process (De Laat et al, 2004;Grebel et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a high concentration of chloride ions, however, the oxidation of aniline ceased. Chloride ions slow down the oxidation reactions through the complexation of Fe 2+ /Fe 3+ with Cl − (Reactions (4)- (7)) and/or by acting as scavengers of hydroxyl radicals (Reactions (8)- (10)) (Bacardit et al, 2007;De Laat et al, 2004;Kiwi et al, 2000;Machulek et al, 2007). It can be seen from Reactions (8) and (10) that the scavenging effect of chloride ions was pH-dependent, which can be abated by maintaining the pH at an optimal level of 3 during the Fenton process (De Laat et al, 2004;Grebel et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Industrial processes, such as oil and gas recovery or crystallization, also generate wastewater of high salinity. Saline wastewater with hydrocarbons can also be found in petroleum-based industry sites, as a result of petroleum spills in the sea or over coastal areas or as a result of accidents during transportation (Bacardit et al, 2007). The presence of inorganic anions (chloride ions and sulfate ions) may weaken the efficiency of oxidation processes based on hydroxyl radicals for the oxidative degradation of organic contaminants (Ratanatamskul et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the photo-Fenton process proceeds, partial degradation of the organic material causes the pH of the medium to fall to ca. pH 2.0, where photolysis of FeCl 2+ dominates over photolysis of Fe(OH) 2+ and where the chloride ion efficiently converts any HO • formed in the system into the intrinsically much less reactive Cl 2 • -radical anion (Bacardit et al, 2007;Buxton et al, 1999;De Laat et al, 2004;George & Chovelon, 2002;Kiwi et al, 2000;McElroy, 1990;Moraes, et al, 2004a;Nadtochenko & Kiwi, 1998;Pignatello, 1992;Soler et al, 2009;Truong et al, 2004;Yu, 2004;Yu et al, 2004;Yu & Barker, 2003a, 2003bZapata et al, 2009). As a result, virtually complete inhibition of the photoFenton degradation of typical organic substrates (Kiwi & Nadtochenko, 2000; www.intechopen.com Moraes et al, 2004aMoraes et al, , 2004bPignatello, 1992) will occur at moderate chloride ion concentrations [>0.03 M NaCl for aliphatic hydrocarbons (Moraes et al, 2004a); >0.2 M NaCl for phenols] when the pH of the medium reaches pH 2.0 or below.…”
Section: Wwwintechopencom Organic Pollutants Ten Years After the Stmentioning
confidence: 99%
“…It has been reported that at pH B3.0, chloride ions in the wastewaters may decrease the efficiency of the oxidation processes, which is attributed to the capture of hydroxyl radicals producing less reactive (than hydroxyl radicals) anion radicals (Bacardit et al 2007) and the complexation of Cl -with Fe 2? /Fe 3?…”
Section: Effect Of Kclmentioning
confidence: 99%